Isolated Increased Nuchal Translucency in First Trimester Ultrasound Scan: Diagnostic Yield of Prenatal Microarray and Outcome of Pregnancy - Stuurman, Kyra E.; van der Mespel-Brouwer, Marjolein H.; Engels, Melanie A. J.; Elting, Mariet W.; Bhola, Shama L.; Meijers-Heijboer, Hanne (Frontiers in Medicine, 2021)
Background Increased nuchal translucency (NT) is associated with aneuploidy. When the karyotype is normal, fetuses are still at risk for structural anomalies and genetic syndromes. Our study researched the diagnostic yield of prenatal microarray in a cohort of fetuses with isolated increased NT and questioned whether prenatal microarray is a useful tool in determining adverse outcome of the pregnancy. Materials and methods 166 women, pregnant with a fetus with isolated increased NT, were offered karyotyping and subsequent prenatal microarray when karyotype was normal. Additionally, all ongoing pregnancies of fetuses with normal karyotype were followed up with regard to postnatal outcome. The follow up time after birth was maximally four years. Results 149 of 166 women opted for prenatal testing. 77 fetuses showed normal karyotype(52%). 73 of 77 fetuses with normal karyotype did not show additional anomalies on early ultrasound. 40 of 73 fetuses received prenatal microarray of whom 3 fetuses had an abnormal microarray result: 2 pathogenic findings (2/40) and one incidental carrier finding. In 73 fetuses with an isolated increased NT, 21 pregnancies showed abnormal postnatal outcome (21/73, 28.8%), 29 had a normal outcome (29/73, 40%) and 23 were lost to follow-up (23/73, 31.5%). 7 out of 73 live born children showed an adverse outcome (9.6%). Conclusion Prenatal microarray in fetuses with isolated increased NT has a 5% (2/40) increased diagnostic yield compared to conventional karyotyping. A normal microarray in fetuses with isolated increased NT, however, still results in a 28.8% risk of pregnancy loss or an affected child.